2012
DOI: 10.1152/ajprenal.00283.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation induces excess diuresis and natriuresis in healthy children

Abstract: Urine production is reduced at night, allowing undisturbed sleep. This study was undertaken to show the effect of sleep deprivation (SD) on urine production in healthy children. Special focus was on gender and children at an age where enuresis is still prominent. Twenty healthy children (10 girls) underwent two 24-h studies, randomly assigned to either sleep or SD on the first study night. Diet and fluid intake were standardized. Blood samples were drawn every 4 h during daytime and every 2 h at night. Urine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 41 publications
2
39
0
2
Order By: Relevance
“…Even more, children with NE clearly have more daytime sleepiness and suffer from sleep deprivation [3]. Mahler et al demonstrated that sleep deprivation might result in increased nocturnal diuresis volume [4]. During polysomnography, our study group observed increased periodic limb movements (PLMS) and cortical arousals in children with refractory NE [5].…”
Section: Introductionsupporting
confidence: 46%
“…Even more, children with NE clearly have more daytime sleepiness and suffer from sleep deprivation [3]. Mahler et al demonstrated that sleep deprivation might result in increased nocturnal diuresis volume [4]. During polysomnography, our study group observed increased periodic limb movements (PLMS) and cortical arousals in children with refractory NE [5].…”
Section: Introductionsupporting
confidence: 46%
“…Yet in an actigraphic case control study, Cohen-Zrubavel et al also confirmed the association between significantly increased sleep fragmentation and daytime sleepiness in children with monosymptomatic NE [12]. The observations of nocturnal polyuria (NP) in sleep-deprived healthy children [16] led us to design the present study consisting of a homogenous population: children with monosymptomatic NE and NP, with exclusion of refractory patients. The aims of the study were: (1) to investigate PLMS and sleep fragmentation by using standardized polysomnography (PSG); 2) to correlate sleep parameters with enuretic parameters (fluid intake, bladder volume, number of wet nights, number of nights with NP), and (3) to compare the PLMS and cortical arousals with our previously reported results in children with refractory NE [13].…”
Section: Introductionmentioning
confidence: 68%
“…The Aarhus group found a substantial increase in diuresis, a higher heart rate, and higher blood pressure with suppressed plasma levels of all sodium-retaining hormones [11].…”
Section: Nocturnal Enuresismentioning
confidence: 99%